Hellboy universe essentials. B.P.R.D. : plague of frogs - Mignola, Mike (Dark Horse Books, 2021)
"Try a taste of the long-running B.P.R.D. series with this introductory volume! Meet Abe Sapien, a senior agent in the Bureau for Paranormal Research and Defense. He and his fellow uncanny agents Liz Sherman, Roger the homunculus, and Johann Kraus uncover his occult origins while try to stop a plague of monstrous frog men. As it begins its spread across America, an apocalyptic new direction to Mignola's stories opens up, the perfect entry point for new readers. Hellboy Universe Essentials: B.P.R.D. is perfect for curious fantasy, horror, and occult readers looking for a taste of something new! It's a fabulous gateway into the B.P.R.D.'s many adventures."--